2022
DOI: 10.3389/fspas.2022.871275
|View full text |Cite
|
Sign up to set email alerts
|

2022 Tonga Volcanic Eruption Induced Global Propagation of Ionospheric Disturbances via Lamb Waves

Abstract: The Tonga volcano eruption at 04:14:45 UT on 2022-01-15 released enormous amounts of energy into the atmosphere, triggering very significant geophysical variations not only in the immediate proximity of the epicenter but also globally across the whole atmosphere. This study provides a global picture of ionospheric disturbances over an extended period for at least 4 days. We find traveling ionospheric disturbances (TIDs) radially outbound and inbound along entire Great-Circle loci at primary speeds of ∼300–350 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

49
170
0
9

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(228 citation statements)
references
References 51 publications
(49 reference statements)
49
170
0
9
Order By: Relevance
“…The disturbance responsible for the observed EEJ and CEJ signatures is most likely related to atmospheric gravity wave activities that were produced by the Tonga volcanic eruption and detected globally within the first few hours of the eruption (Yuen et al, 2022). This volcanic eruption generated a broad spectrum of atmospheric waves, such as gravity waves, that propagated into the upper atmosphere and even affected the F-region ionosphere (Themens et al, 2022;Zhang et al, 2022). By combining space-and ground-based observations, our analysis shows that this disturbance propagated outward (mainly eastward at our observation locations) from the volcano eruption site with a propagation speed in the order of ∼350-400 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance responsible for the observed EEJ and CEJ signatures is most likely related to atmospheric gravity wave activities that were produced by the Tonga volcanic eruption and detected globally within the first few hours of the eruption (Yuen et al, 2022). This volcanic eruption generated a broad spectrum of atmospheric waves, such as gravity waves, that propagated into the upper atmosphere and even affected the F-region ionosphere (Themens et al, 2022;Zhang et al, 2022). By combining space-and ground-based observations, our analysis shows that this disturbance propagated outward (mainly eastward at our observation locations) from the volcano eruption site with a propagation speed in the order of ∼350-400 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…• Ionospheric total electron content (TEC) data reveal that the 15 January 2022 Hunga Tonga volcanic eruption involved at least five large explosions between 4 and 5UT • From TEC observations, we estimate the onset time to be 04:05:54UT and the main explosion energy release of 9-37 Megatons trinitrotoluene equivalent • The eruption-driven shock wave caused an unprecedentedly strong and long-lasting depletion in the ionosphere eruption also generated large ionospheric disturbances that propagated around the world (Themens et al, 2022;Zhang et al, 2022).…”
mentioning
confidence: 99%
“…As such, the ionosphere, readily observed by ground-based instruments, can function as a sensitive monitor of atmospheric disturbances. Initial Total Electron Content (TEC) observations have reported Traveling Ionospheric Disturbances (TIDs) propagating globally for many hours and even days after the Tonga eruption (Aa et al, 2022;Lin et al, 2022;Themens et al, 2022;Zhang et al, 2022). Estimates of the horizontal wavelength of TIDs in the far field (i.e., at distances >3,000 km from the eruption) range from 300 to 1,000 km (Wright et al, 2022;Zhang et al, 2022).…”
mentioning
confidence: 99%
“…Initial Total Electron Content (TEC) observations have reported Traveling Ionospheric Disturbances (TIDs) propagating globally for many hours and even days after the Tonga eruption (Aa et al, 2022;Lin et al, 2022;Themens et al, 2022;Zhang et al, 2022). Estimates of the horizontal wavelength of TIDs in the far field (i.e., at distances >3,000 km from the eruption) range from 300 to 1,000 km (Wright et al, 2022;Zhang et al, 2022). Additionally, Soares et al (2022) reported oscillations of the geomagnetic field observed by a ground-based magnetometer 835 km from Tonga, which are attributed to short-period modulation (3-5 min) of ionospheric currents.…”
mentioning
confidence: 99%